Technologies, Deafness, and Critical Compromise - Guillemin, Marilys; Gillam, Lynn; Brookes, Alison (Disability Studies Quarterly, 2005)
The original aim in this research was to explore the responses of people who identify as Deaf, deaf, or hearing impaired to genetic testing for deafness. Nineteen in-depth interviews were undertaken with Deaf and deaf/hearing impaired people from South East Australia. Analysis showed that there appeared to be a relative acceptance of genetic testing, and a general opposition to cochlear implants. However, further consideration of these responses suggested that there was neither outright rejection or complete acceptance, but rather, a critical engagement and pragmatic reconciliation with these technologies, which we characterize as critical compromise. Critical compromise is a useful concept in understanding how people understand and interact with technologies and the effects of these practices and interactions.